Literasi Kesehatan: Suatu Konsep Analisis - Batubara, Sakti Oktaria; Wang, Hsiu Hung; Chou, Fan Hao (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: to clarify the definition of health literacy and its attributes and provide guideline for future researchMethods: Eight step of concept analysis from Walker and Avant use in this article. Data source use reviewed Â from search engine (Cumulative Index for Nursing and Allied Health, PubMed, Web of Science and Google Scholar), dictionaries, journal articles, and the WHO website, using keywords: health, literacy and health literacy.Results: this concept analysis of health literacy found six attributes such as reading and numerical skill, oral and written communication, comprehension and capability to use and access information. Implication for nursing practice should be encouraged health outcome.Conclusion: Concept health literacy will change quickly depend on many factors. Exsploration needed to develop theory and used in nursing practice, education and research.